علاقات التقابل النصي في آيات النعيم والجحيم في القرآن الكريم - النجّار أشواق محمد إسماعيل; صالح زيار جلال (Al-Adab Journal, 2019)
This research is marked aims (juxtaposition text relations in the verses of bliss and hell in the holy Qur’an) to study a set of relationships that depend upon the script concordance in the verses of bliss and hell, to a statement of meeting the distinction between the two opposite sides of the people of bliss and hell conflict. The research includes four topics , Fajts first section study (relationship juxtaposition script gross and detailed) Dest detail relationship after all, and the relationship of the aggregate after detail, the second topic is marked by (relationship juxtaposition text explanatory), shows the link reasoning between textual unity issues reliable juxtaposition text in verses element heaven and hell, and the third section was titled (relationship juxtaposition script interpretative); to clarify ambiguities say in the verses of bliss and hell, and the fourth section, entitled (relationship juxtaposition script antagonistic), highlights the contrast relationship, which is one of the important pillars in achieving concordance script. The research found to The juxtaposition text is achieved with a set of relationships that accrue to highlight the meanings and friendliness in a variety of scenes in the folds of verses, and is based on the well-organized between the elements of the divine discourse and its components, as a mechanism of clarity and force in the verses of bliss and hell, and showed us the depth of contrast relations Semantic between the two teams and check each.